2022
DOI: 10.1002/cpe.7006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of coefficient of variation using linear moments and calibration approach for nonsensitive and sensitive variables

Abstract: Assessment of coefficient of variation (CV) is of major importance in numerous examinations. However, the appearance of extreme observations raises concerns about the outcomes of CV estimates based on conventional moments. So, motivated by some recent developments in finite sampling theory, we propose some new estimators of CV based on the properties of linear moments (L-moments and Trimmed L-moments), which are highly robust whenever outliers or extreme observations appear in a dataset.The proposed estimators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Shahzad et al [2] introduced a novel family of variance estimators based on L-moments and calibration approach under strati ed simple random sampling (SSRS), whereas Shahzad et al [3] suggested L-Moments and calibration-based variance estimators under double SSRS and discussed an application of COVID-19 pandemic. Shahzad et al [4] considered the estimation of coe cient of variation using L-moments and calibration approach for nonsensitive and sensitive variables, whereas Shahzad et al [5] developed variance estimation based on L-moments and auxiliary information. e estimation of population mean is a widely discussed approach in sample surveys and many renowned authors have utilized these auxiliary pieces of information at estimation stage and suggested various modi ed estimators to date.…”
Section: Introductionmentioning
confidence: 99%
“…Shahzad et al [2] introduced a novel family of variance estimators based on L-moments and calibration approach under strati ed simple random sampling (SSRS), whereas Shahzad et al [3] suggested L-Moments and calibration-based variance estimators under double SSRS and discussed an application of COVID-19 pandemic. Shahzad et al [4] considered the estimation of coe cient of variation using L-moments and calibration approach for nonsensitive and sensitive variables, whereas Shahzad et al [5] developed variance estimation based on L-moments and auxiliary information. e estimation of population mean is a widely discussed approach in sample surveys and many renowned authors have utilized these auxiliary pieces of information at estimation stage and suggested various modi ed estimators to date.…”
Section: Introductionmentioning
confidence: 99%
“…Ratio estimators are often used to estimate the population mean when the correlation between study and auxiliary variables is positively high. Such as Irfan et al, 1 Shahzad et al, 2 and Shahzad et al 3 introduced a class of estimators utilizing supplementary information under simple random sampling scheme when study variable is nonsensitive or sensitive. Shahzad et al 4 proposed a ratio estimator for population variance using L‐Moments and calibration technique.…”
Section: Introductionmentioning
confidence: 99%